2016
DOI: 10.1007/s00122-016-2843-7
|View full text |Cite
|
Sign up to set email alerts
|

Defeating the Warrior: genetic architecture of triticale resistance against a novel aggressive yellow rust race

Abstract: Genome-wide association mapping of resistance against the novel, aggressive 'Warrior' race of yellow rust in triticale revealed a genetic architecture with some medium-effect QTL and a quantitative component, which in combination confer high levels of resistance on both leaves and ears. Yellow rust is an important destructive fungal disease in small grain cereals and the exotic 'Warrior' race has recently conquered Europe. The aim of this study was to investigate the genetic architecture of yellow rust resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 44 publications
8
13
0
Order By: Relevance
“…This difference in heritability is in agreement with YR resistance studies in Triticale (a hybrid between wheat and rye) that also report lower heritability in ears compared to leaves (Losert et al 2017). Furthermore, Losert et al (2017) argue that the severe ear infection they observed in Triticale may have been a feature of the prevalent Pst 'Warrior' race and its potential ability to develop at warmer temperatures.…”
Section: Glume Yr Infection and Phenotypesupporting
confidence: 86%
“…This difference in heritability is in agreement with YR resistance studies in Triticale (a hybrid between wheat and rye) that also report lower heritability in ears compared to leaves (Losert et al 2017). Furthermore, Losert et al (2017) argue that the severe ear infection they observed in Triticale may have been a feature of the prevalent Pst 'Warrior' race and its potential ability to develop at warmer temperatures.…”
Section: Glume Yr Infection and Phenotypesupporting
confidence: 86%
“…The data presented herein are crucial for the breeding of new triticale varieties resistant to CYR34. However, only six QTLs associated with CYR34 were identified, which is fewer than the QTLs related to 'Warrior' detected by Losert et al (2017). In contrast to wheat with its much broader germplasm pool, triticale breeding can currently only exploit the Yr loci available within this man-made crop.…”
Section: Construction Of the Triticale Genetic Linkage Mapmentioning
confidence: 96%
“…QTLs mapping for resistance to the yellow rust race CYR34 QTL mapping approaches can be employed to dissect the genetic architecture underlying complex traits and to identify QTL for marker-assisted selection programs (Alheit et al, 2014). Using genome wide association mapping in triticale, Losert et al (2017) identified 10 QTLs for resistance to the yellow rust pathogen race 'Warrior' on leaves, seven of them were responsible for ear resistance. The exotic 'Warrior' race has conquered Europe in recent years.…”
Section: Construction Of the Triticale Genetic Linkage Mapmentioning
confidence: 99%
See 1 more Smart Citation
“…stem and leaf rust and Fusarium head blight (FHB). The most important, triticale become vulnerable to powdery mildew (Losert et al 2017;Galiano-Carneiro et al 2019) that may lead to signi cant economic losses (Arseniuk and Góral 2015;Mergoum et al 2019).…”
Section: Introductionmentioning
confidence: 99%